MAGNESIUM AND MITRAL VALVE PROLAPSE. EFFICACY AND THE POINTS OF APPLICATION - A. G. Avtandilov; K. M. Dzeranova; A. A. Pukhaeva; E. D. Manizer (Столичная издательская компания, 2016)
Mitral valve prolapse (MVP) is a manifestation of the hereditary syndrome of differentiated or undifferentiated connective tissue dysplasia (CTD). Genetic defect of synthesis and/or degradation of extracellular matrix is the basis of the CTD. MVP is a frequent manifestation of CTD and often is its the main manifestation, despite of the involvement of other organs and systems. Micronutrient deficiencies, especially magnesium one is the mostly important in CTD manifestations. Pathogenetic pharmacotherapy should be comprehensive. Magnesium drugs must necessarily be included in the treatment regimen. Analysis of domestic and international study data on magnesium orotate use in patients with MVP is presented. The results of their own experience of the orotate magnesium use and its possible effect on the inotropic cardiac function in patients with MVP are presented.